ANALISIS PENILAIAN KINERJA DOSEN MENGGUNAKAN METODE BALANCE SCORECARD (STUDI KASUS STT SANGKAKALA) - Ibar Adi Permana (Universitas Semarang, 2020)
The purpose of this study is to assess the performance of lecturers based on the workload of lecturers at the Sangkakala STT institution. During this time the performance evaluation of lecturers is only in the context of Education, so it does not cover the whole implementation of the tri dharma of tertiary institutions carried out by lecturers. The method used in this study is a qualitative method with a balance scorecard approach. Lecturer performance appraisal has 3 strategic objectives namely financial perceptive, customer perspective, and internal business process perspective. While supporting software development in evaluating lecturer performance is a source of data for assessing lecturer performance at the STT Sangkakala institution there are several subsystems, namely: EKEU subsystem, EDOM subsystem, EDOS subsystem, EPRODI subsystem, EPRODI subsystem, EP3M subsystem, and ADAK subsystem